Glycan Therapeutics: Resurrecting an Almost Pharma‐Forgotten Drug Class (Adv. Therap. 8/2018). Issue 8 (10th December 2018) - Paderi, John; Prestwich, Glenn D.; Panitch, Alyssa; Boone, Tom; Stuart, Kate
Abstract : Despite their enormous potential, glycans as therapeutics remain a widely untapped drug class. In article number1800082 John Paderi and co‐workers present a review on glycan therapeutics that are in clinical development or approved for clinical use. The cover image illustrates the heparin‐peptide conjugate SB‐030 binding to collagen exposed in denuded vascular endothelium, and preventing platelet attachment and activation.